Review : overexpression of protein under transcriptional regulation of lambda pL promoter system in Escherichia coli: consequences and bioprocess improvement approaches - Razali, Firdausi; Moo-Young, Murray; Scharer, Jeno M.; Glick, Bernard R. (Faculty of Chemical and Natural Resources Engineering, UTM, 2007)
The attraction of employing thermal induction system in the production of heterologous protein is mainly due to 1) a higher expressed protein titer in comparison to constitutive system, and 2) a cleaner process since no chemical inducing agent is added. However, problems pertaining to high temperature and protein overexpression such as inclusion bodies formations, metabolic overload on the host, stress-related proteolysis on the expressed protein, and enhanced acetic acid secretion are commonly encountered. Several bioprocess approaches that include temperature upshift schemes, feeding strategies, timing of induction, two-stage culture mode, and stabilization of plasmid had been implemented to minimize some of these problems. The approaches are reviewed in this article.